Towards non‐invasive in vivo characterization of the pathophysiological state and mechanical wall strength of the individual human AAA wall based on 4D ultrasound measurements. Issue 12 (19th August 2018) - Wittek, Andreas; Derwich, Wojciech; Fritzen, Claus‐Peter; Schmitz‐Rixen, Thomas; Blase, Christopher
Abstract: Abdominal aortic aneurysms (AAA) are a degenerative disease of the aorta with high associated mortality. Currently, there is a lack of in vivo information, which allows to characterise the individual aneurysmal wall with regard to wall strength or rupture risk. We have used 4D ultrasound strain imaging to compute the spatially resolved distribution of the in‐plane strain tensor and of the local distensibility in three patient groups (young,  < 40 y. o.; elderly,  > 60 y. o.; AAA). Mean and local maximum deformation and distensibility as well as indices for the local variations of the strain and the distensibility distribution were determined. Mean distensibility is significantly decreasing from young (3.83 [2.83, 5.87] 10 −3 mmHg −1 ) to elderly (0.67 [0.39, 0.87] 10 −3 mmHg −1 ) and AAA (0.27 [0.20, 0.54] 10 −3 mmHg −1 ). Both indices characterising the heterogeneous elastic behaviour are significantly increasing from young through elderly to AAA. Linear dependency of some of the distensibility distribution indices on age and aortic diameter was observed in the young and elderly group. In contrast, none of the indices depended on age or maximum diameter in the AAA group. We hypothesize that the heterogeneous distensibility distribution is indicative of microstructural changes in the aortic and aneurysmal wall and might contribute to a more complete and informative pathophysiological characterisation of the AAA wall, either with respect to wall strength or rupture risk. To confirm this hypothesis, further studies will be necessary in which the correlation between the proposed indices and individual wall strength and rupture risk is tested. Abstract : Abdominal aortic aneurysms (AAA) are a degenerative disease of the aorta with high associated mortality. Currently, there is a lack of in vivo information, which allows to characterise the individual aneurysmal wall with regard to wall strength or rupture risk. We have used 4D ultrasound strain imaging to compute the spatially resolved distribution of the in‐plane strain tensor and of the local distensibility in three patient groups (young,  < 40 y. o.; elderly,  > 60 y. o.; AAA). Mean and local maximum deformation and distensibility as well as indices for the local variations of the strain and the distensibility distribution were determined. Mean distensibility is significantly decreasing from young (3.83 [2.83, 5.87] 10 −3 mmHg −1 ) to elderly (0.67 [0.39, 0.87] 10 −3 mmHg −1 ) and AAA (0.27 [0.20, 0.54] 10 −3 mmHg −1 ). Both indices characterising the heterogeneous elastic behaviour are significantly increasing from young through elderly to AAA. Linear dependency of some of the distensibility distribution indices on age and aortic diameter was observed in the young and elderly group. In contrast, none of the indices depended on age or maximum diameter in the AAA group. We hypothesize that the heterogeneous distensibility distribution is indicative of microstructural changes in the aortic and aneurysmal wall and might contribute to a more complete and informative pathophysiological characterisation of the AAA wall, either with respect to wall strength or rupture risk. To confirm this hypothesis, further studies will be necessary in which the correlation between the proposed indices and individual wall strength and rupture risk is tested.